Monetary policy and bank lending in France: are there asymmetries? - Claire Loupias; Frédérique Savignac; Patrick Sevestre (European Central Bank (ECB), 2001)
This paper aims at providing some empirical evidence about the impact of monetary policy on bank lending at the microeconomic level. We estimate a model close to that proposed by Kashyap and Stein (2000) using a panel data set comprising 312 banks observed quarterly over the period 1993-2000. We find that bank lending decreases after a monetary policy tightening. Moreover, as in several other Euro area economies, banks' liquidity appears to impact significantly on their lending behavior
Keywords: E51; E52; G21; 330; credit channel; monetary policy